Metabolomics analysis of dynamic quality changes in beef during low-voltage electrostatic field combined with partial freezing storage - Yuxia Liu; Wei Su; Yingchun Mu; Xiaomin Liu; Kangli Yang; Rongrong Mu (Food Chemistry: X, 2025)
The quality and shelf life of beef are significantly affected by storage conditions, emphasizing the urgent need for efficient preservation technologies to extend shelf life and reduce waste. This study evaluated the quality changes of beef during storage under low-voltage electrostatic field (LVEF) combined with partial freezing and under partial freezing alone. The results showed that during the 0–24 day storage period, LVEF effectively slowed the increases in pH, thiobarbituric acid reactive substances, total volatile basic nitrogen, and total viable counts, maintained tenderness, and delayed protein oxidation. Metabolomics analysis indicated that LVEF inhibited the formation of off-flavors such as hexanal, 1-octen-3-ol, and benzaldehyde, and reduced the loss of inosine monophosphate, thereby preserving beef quality. Metabolic network analysis further revealed that these metabolites were closely associated with the metabolism of fatty acids, phenylalanine, and proline. These findings suggest that LVEF can effectively enhance the storage quality of beef.